'In the heart, there's nothing': unruly youth, generational vertigo and territory. Issue 4 (10th October 2012) - Smith, Sara H
<x xml:space="preserve">Abstract</x> Young Ladakhis have grown up along disputed borders between Pakistan and China in India's Jammu and Kashmir State. During their lifetimes, conflict in Kashmir and in their hometowns (between the Buddhist majority and Muslim minority) has highlighted the region's geopolitical vulnerability; in words overheard in the schoolyard and kitchen, religion is always already political and territorial. This article traces how young Muslim and Buddhist Ladakhis in Ladakh's Leh District are constituted as a category and site of territorial potential, and how the young people I spoke with navigate and elude this positioning. Their grandparents married across religious lines and their parents used family planning enthusiastically, but these practices are now political problems. Youth alternate between cynicism and hopeful visions of the future. Meanwhile, parents see education in distant urban centres as a path to a desired 'modernity', but also as a dangerous site where unruly love, lack of supervision and immorality might compromise religious identity. Building on geographies of young people and religion, and on anthropologies of the future, this research draws on two youth projects, a survey and interviews. I suggest that parents, political actors and religious leaders conceive of the young as crucial to the constitution of future territories. This makes their bodies a site of intense anxiety and regulation, as well as hope and potential. Beyond this case study, I offer the concept of generational vertigo, a mixture of apprehension and anticipation regarding the future, and suggest that attending to how and why this vertigo is manifest provides a way to think through relationships between young people, time and territory. The future is located in the volatile bodies of young people; hence the desire to defend territory and shape the future is manifest in attempts to manage the potential of these bodies.